Rewiring the Drosophila Brain With Genetic Manipulations in Neural Lineages - Sullivan, Luis F. (Frontiers in Molecular Neuroscience, 2019)
Neurons originate from neural stem cells and then synapse with stereotyped partners to form neuronal circuits. Recent findings indicate that several molecular mechanisms generating neuronal identity can rewire neuronal connectivity in the Drosophila brain when genetically manipulated. In this review, I discuss how mechanisms generating neuronal identity could activate molecular pathways essential for circuit formation and function. Next, I propose that the central complex of Drosophila, an ancient and highly conserved brain region essential for locomotor control and navigation, is an excellent model system to further explore mechanisms linking circuit development to circuit function.